(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
A consistent pattern of behaviour that violates others fundamental rights or disregard social norm is considered to be an indication of conduct disorder. As listed in the DSM-V, symptoms typically include aggression to people and animals, destruction of property, deceitfulness or theft and serious violation of rules. These behaviours are typically displayed by children and adolescents in a variety of settings- at home, at school, and in social situations and they cause remarkable impairment in his or her social, academic or occupational functioning. A 10 year old boy presented with lying, lack of concentration, skipping school, running away from home and stay out night, sexual talks, stealing money, increased anger, disrespect towards elders and suicidal talks from last 4 years was admitted in Government Ayurveda Research Institute for Mental Health and Hygiene, Kottakkal. Based on Dosha predominance, it was diagnosed as Vata-Pitta Unmada. Accordingly he was treated with Ayurvedic internal medication and procedures including Virechana, Shirodhara, Snehapana, Abhyanga, Ushmasweda and Pratimarsa nasya for 21 days along with 1 session of CBT. Conduct disorder rating scale parent version was used to evaluate symptoms before and after treatment. Problems caused by him in school and home reduced from severe to mild. Internal medication continued for 3 months and monthly review was taken. On assessment after 3 months his anger got reduced, he is going to school regularly and did not run away from home over night. This case report shows that conduct disorder can be treated effectively with Ayurvedic management along with cognitive behavioral therapy.